2023
DOI: 10.1111/jsr.13977
|View full text |Cite
|
Sign up to set email alerts
|

Self‐applied somnography: technical feasibility of electroencephalography and electro‐oculography signal characteristics in sleep staging of suspected sleep‐disordered adults

Matias Rusanen,
Henri Korkalainen,
Heidur Gretarsdottir
et al.

Abstract: SummarySleep recordings are increasingly being conducted in patients’ homes where patients apply the sensors themselves according to instructions. However, certain sensor types such as cup electrodes used in conventional polysomnography are unfeasible for self‐application. To overcome this, self‐applied forehead montages with electroencephalography and electro‐oculography sensors have been developed. We evaluated the technical feasibility of a self‐applied electrode set from Nox Medical (Reykjavik, Iceland) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Nevertheless, future studies utilizing longer-term monitoring to assess habitual sleep patterns, such as with actigraphy, would be helpful in confirming our results. Although all sleep stages were observed, participants in the study demonstrated a low proportion of N3 sleep, which is due to the limitations of using the self-applied forehead EEG signals that have higher impedances leading to attenuated voltages of observed delta waves [ 90 ]. Thus, the limited EEG utilized may have affected the study’s power to evaluate differences in this sleep stage on T lymphocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, future studies utilizing longer-term monitoring to assess habitual sleep patterns, such as with actigraphy, would be helpful in confirming our results. Although all sleep stages were observed, participants in the study demonstrated a low proportion of N3 sleep, which is due to the limitations of using the self-applied forehead EEG signals that have higher impedances leading to attenuated voltages of observed delta waves [ 90 ]. Thus, the limited EEG utilized may have affected the study’s power to evaluate differences in this sleep stage on T lymphocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to the traditional EEG montage offered by Nox Medical is the Self Applied Somnography (SAS) setup (Nox Medical, Reykjavik, Iceland), which is a simplified EEG montage that positions 10 stick-on electrodes along the forehead and near the eyes to capture prefrontal cortex EEG (AF8, AF4, GND, AFz, AF3, AF7) and EOG (E1, E2, E3, E4) activity without recording the mastoid channels. 94 95 Chin EMG is also omitted, although an EMG signal derived from the eyes is available for analysis. 94 95 Since EEG setups may fail to accommodate thick hair types or various hairstyles, offering the SAS setup as an alternative, but valid, 94 95 approach to in-home sleep monitoring may promote a more culturally inclusive method for individuals who are unable to or prefer not to use the traditional PSG setup with Ten20 paste adhesion.…”
Section: Methods and Analysismentioning
confidence: 99%
“… 94 95 Chin EMG is also omitted, although an EMG signal derived from the eyes is available for analysis. 94 95 Since EEG setups may fail to accommodate thick hair types or various hairstyles, offering the SAS setup as an alternative, but valid, 94 95 approach to in-home sleep monitoring may promote a more culturally inclusive method for individuals who are unable to or prefer not to use the traditional PSG setup with Ten20 paste adhesion.…”
Section: Methods and Analysismentioning
confidence: 99%